THE EFFECT OF THE MOTIVATION OF AVOIDING RIBA AND KNOWLEDGE OF SHARIA BANKING PRODUCTS ON THE DECISION TO BECOME A CUSTOMER AT PT. BANK MUAMALAT INDONESIA TBK KC PADANGSIDIMPUAN - heni mutiara; Windari windari; ali hardana; syuaib nasution (Journal Of Sharia Banking, 2020)
This study aims to determine the significant influence between motivation to avoid usury and knowledge of Islamic banking products on the decision to become a customer at PT. Bank Muamalat Indonesia Tbk KC Padangsidimpuan. The method used in this research is descriptive quantitative. The data collection techniques used were questionnaires and documentation. Sampling in this study using random sampling with a sample size of 99 people. To simplify the data analysis process, this research was assisted by the SPSS version 23 program. The t test results indicate that there is a significant influence between motivation to avoid usury and knowledge of Islamic banking products on the decision to become a customer. Based this shows that the influence of the motivation variable to avoid usury and knowledge of Islamic banking products on the customer satisfaction variable.